2020
DOI: 10.3126/jnphyssoc.v6i1.30555
|View full text |Cite
|
Sign up to set email alerts
|

Variation of GPS- Tec Measurements of the Year 2014: A Comparative Study with IRI - 2016 Model

Abstract: Total Electron Content (TEC) measured from Global Positioning System (GPS) receivers at latitude of 29.17°N and longitude of 80.62°E in Bardiya and TEC derived from IRI- 2016 model is compared for the year 2014, which is geo- magnetically active year. To find out the reliability of IRI-2016 model, comparative study of GPS- TEC and IRI- TEC is very helpful for the study of TEC variations. In this work diurnal, day to day, month to month and seasonal variations of GPS- TEC and IRI- TEC are analyzed. The comparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In general, the plots show that VTEC is maximum during spring followed by autumn, summer and winter, except for a few cases. Similarly, pre-vious studies of GPS TEC for the year 2014 over Nepal also reported the highest value of VTEC in March and lowest in December, with distinct the seasonal variations and having higher values in spring and lower in the winter season (Ghimire et al, 2020b). During the sunspot minimum years of 2008-2010, there are no semiannual variations in the VTEC, and it also seems that the summer VTEC is as strong as the autumn VTEC.…”
Section: Seasonal Variation In Tecmentioning
confidence: 73%
See 2 more Smart Citations
“…In general, the plots show that VTEC is maximum during spring followed by autumn, summer and winter, except for a few cases. Similarly, pre-vious studies of GPS TEC for the year 2014 over Nepal also reported the highest value of VTEC in March and lowest in December, with distinct the seasonal variations and having higher values in spring and lower in the winter season (Ghimire et al, 2020b). During the sunspot minimum years of 2008-2010, there are no semiannual variations in the VTEC, and it also seems that the summer VTEC is as strong as the autumn VTEC.…”
Section: Seasonal Variation In Tecmentioning
confidence: 73%
“…The lower atmospheric disturbance also contributes to ionospheric variability (Anderson and Fuller-Rowell, 1999;Prikryal et al, 2010). Numerous periodic and aperiodic variabilities identified in the ionosphere make the impact on the applications involving the radio link between satellites and the ground, which plays vital role in the communication, navigation and surveillance, with important consequences for the reliability and accuracy of the service (Guo et al, 2015). The global positioning system (GPS) is widely used in recent appliances which encounter the largest errors in the path due to disturbed ionospheric free electrons, emphasizing the need to study GPS-TEC variability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…where, , is the mean radius of the earth in; , the ionosphere (effective) height above the earth's surface; Z, the zenith angle; and E, the elevation angle in degrees [7]. Rama Rao et al (2006) [9] observed that the IPP (Ionospheric Pierce Point) attitude of 350 km is valid for the satellite elevation angle greater than 20°. A GPS receiver can lock the signal of more than one satellite at a time at different angle of elevation from the receivers.…”
Section: Methodsmentioning
confidence: 99%
“…In past years, GPS has become an important tool to study ionospheric character [5 6 7 8]. Due to increment in demand of GPS-based navigation appliances in satellites, aircrafts and other transportations, the study of TEC is heightened [9]. The GPS-TEC is the total number of electrons in a vertical column of 1 cross-section from the height of the GPS satellite (~ 20,000 km) to the receiver on the ground.…”
Section: Introductionmentioning
confidence: 99%